Application of Services in Increasing Consumer Satisfaction - Riyanita, Kenik; Abidin, Zaenal; Munip, Al (Zabags International Journal of Economy, 2025)
The services in this study are: first, how the service increases consumer satisfaction in the shafi'i store. Second, what are the obstacles faced by Toko Syafi'i in increasing consumer satisfaction. This type of research uses qualitative research with a descriptive approach. The types of data collected in this study consist of primary data and secondary data. the qualitative approach is the application of a natural approach to the study of a problem related to individuals, phenomenal, symbols, documents, and social phenomena. The step taken is to collect information about the application of services in increasing consumer satisfaction at paju traders in the traditional market of Dendang DistrictThe results of the research: first, how the service provided by the shafi'i store in increasing the satisfaction of its customers, which must be in demand by many customers and many people. Second, what are the obstacles faced by shafi'i stores in increasing consumer satisfaction, the solution is to create services that are in accordance with the rules and provide quality products.